Diet and Nutrition Risk Factors in Adults Seen in a Dental School Clinic. (14th June 2022) - Rodriguez, Nancy; Samavat, Hamad; Touger-Decker, Riva; Singer, Steven; Duda, Peter; Zelig, Rena
Abstract: Objectives: To determine the prevalence of patient-reported diet and nutrition risk factors related to oral health of adults who attended an undergraduate dental school clinic. Associations between risk factors were also explored. Methods: This was a cross-sectional study of data from adult patients 18–89 years of age (N = 1071) who received care at an urban northeast undergraduate dental school clinic between 2016 and 2021 for whom a Diet and Nutrition Risk Evaluation form was completed as part of routine comprehensive care. Demographic and clinical characteristics, and frequency of diet and nutrition risk factors, were obtained from the electronic health record. Chi-square and Fisher's exact tests were used to determine associations between risk factors. Results: Among those with available demographic data, 55.9% were female (n = 599), 55.4% were White (n = 222), and 61.6% were non-Latino (n = 236). The median age and BMI were 55.0 years and 27.5 kg/m 2 respectively. The six most prevalent diet and nutrition risk factors in the total sample, in descending order were: overweight/obesity (n = 723, 69.1%); dietary supplement use (n = 571, 54.4%); < 3 servings of milk, yogurt, or cheese daily (n = 534, 51.0%); dental caries (n = 525, 50.9%); intake of sugar sweetened beverages (SSB), gum or candy between meals (n = 353, 33.1%); and periodontal disease that interferes with eating (n = 203, 19.3%). Those with dental caries were significantly more likely to consume SSB, gum, or candy between meals and more than 4 times a day than those without dental caries (38.5% vs 27.3%; P < 0.001 and 18.6% vs 12.2%; P = 0.004, respectively). Conclusions: In this sample, the prevalence of overweight/obesity and dental caries were high; consumption of SSB, gum, or candy was strongly associated with dental caries. Identification of diet and nutrition risk factors relative to oral health can be used to design education and interprofessional collaborative endeavors and referrals to enhance patient-centered care. Funding Sources: None.